(untitled) (Sustainability in Debate, 2015)
It is a consensus that the function and structure of the human and environmental systems are complex when analyzed in an isolated and/or integrated way. This subject is part of a current debate about sustainability. In this sense, this research has the goal of offering a literature review about the complexity of the integration between the human and environmental systems, and its relation with the concept of sustainability. This is a qualitative study with an exploratory descriptive design as to the method, and a bibliographical review As to the technical procedures. The results reveal that the idea of sustainability is only feasible when the functioning of the human and environmental systems are observed, because the process of co-evolution, or panarchy, must be considered when identifying the elements or subsystems which should be preserved or kept. Comprehending the complexity of the interactions of the human and environmental systems is essential when defining the idea of sustainability, because they evidence the essence of its purpose.